Suprachoroidal CLS-TA for non-infectious uveitis: an open-label, safety trial (AZALEA). Issue 6 (5th February 2021) - Henry, Christopher Ryan; Shah, Milan; Barakat, Mark R; Dayani, Pouya; Wang, Robert C; Khurana, Rahul N; Rifkin, Lana; Yeh, Steven; Hall, Colette; Ciulla, Thomas
Abstract : Purpose: To evaluate local and systemic safety of suprachoroidal (SC) triamcinolone acetonide injectable suspension (CLS-TA) injections in subjects with non-infectious uveitis (NIU). Design: Open-label, prospective multicentre safety study. Participants: Thirty-eight subjects with NIU, with and without macular oedema (MO). Methods: Treatment consisted of two suprachoroidal injections of CLS-TA 4 mg, 12 weeks apart. Best-corrected visual acuity (BCVA), adverse event (AE) assessment, ophthalmic examinations and optical coherence tomography (OCT) were conducted every 4 weeks for 24 weeks. Blood samples were analysed for plasma triamcinolone acetonide (TA) concentrations. Main outcome measures: The main outcome measure was frequency of AEs. Other endpoints included plasma TA concentrations, change in signs of inflammation, BCVA and retinal central subfield thickness (CST). Results: Based on a CST of >300 µm, 20 out of 38 subjects had MO at baseline. Mean intraocular pressure (IOP) was 13.3 mm Hg at baseline and 15.2 mm Hg at week 24 in the study eye. A total of six (15.8%) subjects had an IOP rise >10 mm Hg compared with baseline, in the study eye, and two (5.3%) subjects had IOP >30 mm Hg (maximum 34 mm Hg at week 8 and 38 mm Hg at week 20). Cataract formation AEs were reported in four study eyes; one of which was deemed treatment-related. No serious ocular AEs in the study eye occurred in the study. Quantifiable post-injection TA plasma concentration was <1 ng/mL. Efficacy parameters showed improvement over the 24-week study period. Conclusions: Suprachoroidally administered CLS-TA was safe and well tolerated over the 24-week, open-label study in NIU subjects with and without MO.